CheckMate 141: 1‐Year Update and Subgroup Analysis of Nivolumab as First‐Line Therapy in Patients with Recurrent/Metastatic Head and Neck Cancer. (4th June 2018) - Gillison, Maura L.; Blumenschein, George; Fayette, Jerome; Guigay, Joel; Colevas, A. Dimitrios; Licitra, Lisa; Harrington, Kevin J.; Kasper, Stefan; Vokes, Everett E.; Even, Caroline; Worden, Francis; Saba, Nabil F.; et al.
Abstract: Nivolumab significantly improved overall survival (OS) vs investigator's choice (IC) of chemotherapy at the primary analysis of randomized, open‐label, phase 3 CheckMate 141 in patients with recurrent or metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN). Here, we report that OS benefit with nivolumab was maintained at a minimum follow‐up of 11.4 months. Further, OS benefit with nivolumab vs IC was also noted among patients who received first‐line treatment for R/M SCCHN after progressing on platinum therapy for locally advanced disease in the adjuvant or primary (i.e., with radiation) setting. Abstract : Results of the CheckMate 141 trial are reported, highlighting outcomes among patients who received nivolumab compared with investigator's choice of therapy as first‐line treatment for patients with recurrent or metastatic squamous cell carcinoma of the head and neck after progressing on platinum therapy for locally advanced disease.